Review of Promoting Energy Sustainability In Iraq: A Comprehensive Vision For The Application and Development of Renewable Energy - S.mohammed, Ghada (Journal of Madenat Alelem University College, 2024)
The importance of using and investing in renewable energy (green energy or clean energy) as alternative energy or supplement to non-renewable energy, such as fossil fuel, is accelerating at present. Renewable energy is considered one of the main axes towards the transition to a sustainable energy system, confronting the growing global demand for energy and filling the economic crisis in addition to the prominent role in preserving the environment, reducing harmful emissions, and adapting to the effects of climate change. The wide spread of renewable energy applications also resulted in a noticeable decrease in the cost of electrical energy produced, especially from the two energy sources (solar and wind energy, while Its use in the areas of heat production, heating) or in the transportation sector is still much less. In this research, the issue of renewable energy was reviewed in Iraq, which is considered one of the countries that deal with alternative energy sources timidly despite the availability of sources such as sun, wind and water, illustrating the importance of investing in renewable energy in Iraqas Iraq needs a specific and clear strategy to deal with energy and to set goals and plans to achieve maximum benefit from it and invest it optimally, also determine the main challenges that affecting renewable energy sources. We also review the alternative energy sources available in Iraq to find out whether it is feasible to rely on them entirely or if there is a need to rely on non-renewable fuels at the same time to meet Iraq’s needs in various areas of production for energy. Additionally, this research focuses on the prospects of different renewable resources and energy in Iraq to enhance its economic recovery, whether in the production or consumption sectors.